European Instructional Lectures Volume 12, 2012, 13th EFORT Congress, Berlin, Germany - Bentley, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This twelfth volume in the EUROPEAN INSTRUCTIONAL LECTURES series continues the format of educational chapters from across Orthopaedics and Traumatology contributed by distinguished Orthopaedic Educators in Europe.   It provides current material and major advances covering a range of topics including:   General Orthopaedics, Basic Science and Technology Musculo-skeletal Tumours Infections Paediatric Orthopaedics Trauma Spine Upper Limb Hip Knee Leg, Ankle and Foot   All the lectures were presented at the 13th EFORT Congress in Berlin, Germany. The Lectures are an authoritative source of information illustrated by radiographs, CT's, MRI scans, and other relevant contemporary imaging modalities, operative photographs, line drawings and tables. They are an invaluable source of instruction for Surgeons and Trainees alike.   This book was edited by Professor George Bentley, Chairman, Scientific Publications Committee of EFORT.
Bone & joint tumours: Multimodel approach to metastatic diseases. Rehabilitation: Multimodal treatment of back pain. Infection: Infection in the spine -- Acute infection after osteosynthesis -- Paediatrics: How to manage osteolytic lesions - diagnosis and treatment. Hip: Hip dysplasia - a problem solved? Polytrauma / pelvis: Damage control in orthopaedics. Trauma upper limb: Proximal humerus fractures. Trauma lower limb: Proximal femur fractures -- Ankle fractures -- Hip: New trends in avascular necrosis of the femoral head -- Navigation and hip surgery -- Recementing in revision total hip replacement -- Instability following THR. Knee osseous: Treatment of osteonecrosis of the knee -- Indications for knee arthroplasty -- Patellar fracture and dislocation -- Arthroscopic treatment of intraarticular fractures of the knee -- Rehabilitation after knee surgery. Foot & ankle: Metatarsalgia treatment -- Management of Ankle Osteoarthritis.
Keywords: Orthopedics; Orthopedics; Surgical Orthopedics; Conservative Orthopedics